Renewable power interface based rural telecom - W. Margaret Amutha; H. Caleb Andrew; A. Debie Shajie; J. Praveen Immanuel Paulraj (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
To power remote area telecom where grid supplied electricity is unreliable, an alternative exists in the form of renewable energy sources. These sources mainly rely on the weather condition of a particular area for their source of power. To overcome such problem, hybridization of energy sources are prefered. Hybridization of solar-wind systems use a separate converter for each source thus leading to a complex, bulky and less efficient system. This paper presents a single renewable power interface which allows solar and wind  sources to supply the load separately or simultaneously depending on the availability of the energy sources. It uses cuk and sepic converter topologies to form cuk-seic interfece. These systems  also use battery backup to store excess energy and to make best use of their operating characteristics. Performance comparison between a cuk-sepic renewable power interface with and without MPPT using MATLAB/SIMULINK is presented. A detailed componentwise analysis is also done to calculate best efficient interface. It is found that the cuk-sepic interface with MPPT is efficient. A lab level model for cuk-sepic interface is developed and tested. The experimental results proved the effective operation of a single renewable power cuk-sepic interface with MPPT.